Physician migration at its roots: a study on the factors contributing towards a career choice abroad among students at a medical school in Pakistan - Sheikh Asfandyar; Naqvi Syed Hassan; Sheikh Kainat; Naqvi Syed Hassan; Bandukda Muhammad (BMC, 2012)
Abstract Background Physician migration, also known as "brain drain," results from a combination of a gap in the supply and demand in developed countries and a lack of job satisfaction in developing countries. Many push and pull factors are responsible for this effect, with media and internet playing their parts. Large-scale physician migration can pose problems for both the donor and the recipient countries, with a resulting reinforcement in the economic divide between developed and developing countries. The main objectives of our study were to determine the prevalence of migration intentions in medical undergraduates, to elucidate the factors responsible and to analyze the attitudes and practices related to these intentions. Methods This was a cross-sectional, observational, questionnaire-based study, conducted at Dow Medical College of Dow University of Health Sciences, Karachi, between January, 2012 and May, 2012. A total of 323 students responded completely. The questionnaire consisted of 3 sections, and was aimed at collecting demographic details, determining students' migratory intentions, evaluating reasons for and against migration and assessing attitudes and practices of students related to these intentions. Results Out of 323 respondents, 195 wanted to pursue their careers abroad, giving a prevalence rate of 60.4% in our sample. United States was the most frequently reported recipient country. The most common reasons given by students who wished to migrate, in descending order, were: lucrative salary abroad followed by quality of training, job satisfaction, better way of life, relatives, more opportunities, better working environment, terrorism in Pakistan, harassment of doctors in Pakistan, desire to settle abroad, more competition in Pakistan, better management, peer pressure, longer working hours in Pakistan, religious reasons, parent pressure, political reasons and favoritism in Pakistan. A considerable number of respondents had already started studying for licensing examinations, and were also planning of gaining clinical experience in their desired country of interest. Conclusion Physician migration is a serious condition that requires timely intervention from the concerned authorities. If considerable measures are not taken, serious consequences may follow, which may pose a threat to the healthcare system of the country.